2020
DOI: 10.1111/josh.12978
|View full text |Cite
|
Sign up to set email alerts
|

School Mental Health Curriculum Effects on Peer Violence Victimization and Perpetration: A Cluster‐Randomized Trial

Abstract: BACKGROUND: Addressing school violence is an important public health goal. To assess the role of school mental health curricula in violence prevention, we evaluated effects of an anti-stigma curriculum on violence victimization/perpetration. METHODS: An ethnically/socioeconomically diverse sample of 751 sixth-graders (mean age 11.5 years) across 14 schools in Texas were block-randomized by school (2011-2012) to receive singly or in combination: (1) a mental illness anti-stigma curriculum; (2) contact with 2 yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…First, our results indicated that school bullying was common among Chinese adolescents, and anti-school bullying prevention programs to reduce the prevalence of school bullying conducted both in the school and in family are essential for school bullying perpetrators and victims ( 43 ). At the same time, health education and promotion for adolescents who were involved in any type of school bullying are also needed ( 44 ). Second, our findings highlight the need for network regulations for teenagers as the associations between VVGE and school bullying behaviors, especially physical school bullying, were positive among Chinese adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…First, our results indicated that school bullying was common among Chinese adolescents, and anti-school bullying prevention programs to reduce the prevalence of school bullying conducted both in the school and in family are essential for school bullying perpetrators and victims ( 43 ). At the same time, health education and promotion for adolescents who were involved in any type of school bullying are also needed ( 44 ). Second, our findings highlight the need for network regulations for teenagers as the associations between VVGE and school bullying behaviors, especially physical school bullying, were positive among Chinese adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In the long run, negative emotions such as fear, dread, and anxiety continue to build up, making them more likely to develop suicidal ideation. 54 Therefore, it is necessary to prevent suicidal tendencies among teenagers by putting an end to school bullying, cultivating their views on life and values, and raising their legal awareness. Relevant authorities should work together with schools to refine the relevant regulations and deal with abusers in strict accordance with the law and school rules and regulations.…”
Section: Eliminating School Bullying Is An Effective Way To Reduce Ad...mentioning
confidence: 99%